Porcine specific real-time polymerase chain reaction (PCR) for halal verification - Khalid, Farihah Liyana; Mustafa, Shuhaimi; Che Man, Yaakob; Sazili, Awis Qurni; Azmi, Aida Azrina; Abdul Rahim, Raha (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
A porcine-specific real-time polymerase chain reaction (PCR) detection of a region in the mitochondrial DNA was developed for Halal verification. A pair of porcine-specific primers was designed to generate a specific fragment of the porcine DNA. To verify the specificity of the primers designed, the primer pair was tested against ten samples to detect any possible crossreactions. The reaction only amplified porcine DNA at Ct 25.03 ± 0.33. The real-time PCR assay employed in this work was proven to be very sensitive with a low detection limit. The assay was done by preparing a 10-fold dilution series to determine the sensitivity of the reaction. The sensitivity threshold was up to 0.001ng porcine DNA.